What Role for Safety Net Transfers in Very Low Income Countries? - Weigand, Christine (World Bank, Washington, DC, 2012)
In countries where large parts of the population live in absolute poverty, the need for social safety nets may be greatest, but the capacity to fund and administer them can be severely constrained. What role can social safety net programs play in very low income countries (VLICs)? Three major challenges must be faced when deciding what programs would be feasible in a VLIC: Availability of information; Administrative capacity; and, Affordability. Some special considerations of certain types of interventions apply in the specific context of VLICs: Cash transfers; Food and nutrition programs; and, Agricultural inputs. Given the need to strike a balance between investments for growth and transfers - both compete for scarce public resources - it may be helpful to follow these steps when deciding on the type and scope of social safety net programs: Re-examine the main constraints to growth and the role of public investment policy; Conduct a vulnerability assessment and identify the main risks confronting poor people; and, Identify policy interventions that have a potential both for reducing vulnerability and for enhancing growth prospects.